Neisseria meningitidis as a Cause of Septic Arthritis: An Unusual Case of Periprosthetic Joint Infection. (10th March 2020) - Mc Carthy, A.; Broderick, J. M.; Molloy, A. P.
Abstract : One of the most feared complications after arthroplasty is infection due to its significant impact on patient morbidity. Infection may transfer to the joint at the time of surgery or be seeded, haematologically, to the prosthetic joint from another infection source. In this case, a 72-year-old female presented with symptoms of septic arthritis seven years after her original arthroplasty surgery. At presentation, she denied trauma and any comorbidity which would predispose her to infection. Culturing of samples taken revealed the patient was infected with Neisseria meningitidis, and the patient underwent a DAIR procedure. She continued postoperative long-term antimicrobial therapy with resolution of her infection. Follow-up at one year showed complete resolution of the patient's illness with a return to premorbid baseline. To our knowledge, this is the third reported case of septic arthritis caused by Neisseria meningitidis in a prosthetic joint in the literature.